2005
DOI: 10.1021/ja051019a
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Weak CH···O Hydrogen Bonds in Maltose Anomers by a Combination of Calculation and Experimental Solid-State NMR Spectroscopy

Abstract: Two-dimensional (1)H-(13)C MAS-J-HMQC solid-state NMR spectra of the two anomeric forms of maltose at natural abundance are presented. The experimental (1)H chemical shifts of the CH and CH(2) protons are assigned using first-principles chemical shift calculations that employ a plane-wave pseudopotential approach. Further calculations show that the calculated change in the (1)H chemical shift when comparing the full crystal and an isolated molecule is a quantitative measure of intermolecular C-H...O weak hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
226
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(243 citation statements)
references
References 47 publications
17
226
0
Order By: Relevance
“…1) (23, 66 -69); thus, we sought to verify our experimental chemical shift change using quantum chemistry calculations. Although this combination of techniques has been used to identify CH⅐⅐⅐O hydrogen bonds in small organic molecules (37,70,71) and in computational biology (68), it has, to our knowledge, not yet been applied experimentally in biological macromolecules. Using this combination of techniques, we reasoned that it should be possible to solve for the hydrogen positions and, thus hydrogen bonding patterns, of the AdoMet methyl group within the SET7/9 active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (23, 66 -69); thus, we sought to verify our experimental chemical shift change using quantum chemistry calculations. Although this combination of techniques has been used to identify CH⅐⅐⅐O hydrogen bonds in small organic molecules (37,70,71) and in computational biology (68), it has, to our knowledge, not yet been applied experimentally in biological macromolecules. Using this combination of techniques, we reasoned that it should be possible to solve for the hydrogen positions and, thus hydrogen bonding patterns, of the AdoMet methyl group within the SET7/9 active site.…”
Section: Resultsmentioning
confidence: 99%
“…Current methods for identifying are difficult to employ for many proteins, including SET7/9. However, NMR spectroscopy holds promise in identifying CH⅐⅐⅐O hydrogen bonds in proteins and other macromolecules via 1 H chemical shift (23,36,37). Recent structural and functional studies have suggested that CH⅐⅐⅐O hydrogen bonds play pivotal roles in substrate binding and catalysis in SET domain KMTs (6,38,39).…”
mentioning
confidence: 99%
“…However, it is only with the development of 1 H homonuclear decoupling schemes suitable for application under moderate to fast MAS frequencies, e.g., Frequency-Switched Lee-Goldburg (FSLG), 5 Phase-Modulated Lee-Goldburg (PMLG), 6 and DUMBO, 7 coupled with advances in RF consoles, that such experiments have started to be more widely employed. 8,9 For example, 13 C, 1 H heteronuclear correlation (HETCOR) experiments at moderate to fast MAS frequencies 10,11 have been widely applied to a variety of significant material types, such as proteins, 12,13 pharmaceuticals, 14,15 silica-supported catalytic complexes, 16,17 organic-templated microporous materials, 18 inorganic-organic hybrid materials, 19 as well as chemical problems, such as the characterisation of weak hydrogen bonding in sugars 20 and the solution of structures from powder diffraction data. 21 Heteronuclear 13 C{ 1 H} spin-echo experiments employing 1 H homonuclear decoupling during the a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The principal components of the resulting shielding tensor were obtained by diagonalizing its symmetric part. Chemical shifts are measured relative to a reference frequency with their direction opposite to the shielding, so the isotropic chemical shift was calculated from the isotropic average of the shielding tensor according to [31][32][33]. To compare with experimental data two-dimensional anisotropic-isotropic correlation spectra were simulated using SIMPSON from the calculated principal components of all 16 1 H sites using the measured B1 distribution and the experimental ν2 linewidths obtained from the 1 H ultrafast MAS spectrum.…”
Section: Computationalmentioning
confidence: 99%